El manejo informativo del desplazamiento forzado en dos medios electrónicos colombianos: eltiempo.com y semana.com (2013)
This article presents the conclusion of a research about electronic media information in Colombia about forced displacement. The objective is to suggest that, in spite of the fact that mass media is a source of information that most people use, only few of them offer precise information. This trend contributes to keep their audiences away from knowing the actual situation, as well as to make it difficult to take actions regard it.